Practical preservation and conservation strategies for libraries - Baird, Brian J. 1966- (Rowman & Littlefield, 2018)
"Designed as a "how-to" manual, Practical Preservation and Conservation Strategies for Libraries provides librarians with information to help them grapple with specific preservation challenges by identifying areas of concern, optimizing the use of resources put towards preservation, and establishing goals for continual improvement over time."-- Provided by publisher.